BROAD-SPECTRUM ANTIBACTERIAL AND ANTIOXIDANT POTENTIALS OF AQUEOUS SYZYGIUM CUMINI (L.) SKEELS LEAF EXTRACT - Yusuf-Salihu, Bashirat O.; Abdulmumini, Shakirat A.; Adedayo, Majekodunmi R.; Muhammad, Adulrahman; Uthman-Saheed, Lateefah (FUDMA JOURNAL OF SCIENCES, 2025)
The worldwide increase in antimicrobial resistance and illnesses associated with oxidative stress has heightened the quest for plant-derived alternatives possessing dual therapeutic benefits. In traditional medicine, Syzygium cumini (L.) Skeels is highly valued for its natural bioactive compounds. This research examined the antibacterial and antioxidant properties of its aqueous leaf extract employing standard in vitro techniques. The antibacterial efficacy was assessed against Escherichia coli, Klebsiella oxytoca, Pseudomonas aeruginosa, Staphylococcus aureus, and Proteus mirabilis using a turbidimetric assay, with the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) established through broth dilution and subculturing methods. The extract exhibited concentration-dependent inhibition in all bacterial strains, with MIC values between 60 and 80 mg/mL and MBC values from 80 to 100 mg/mL. MBC/MIC ratios of 1.67 indicate a bactericidal mechanism of action. Antioxidant activity, evaluated using DPPH and hydrogen peroxide (HO) scavenging assays, showed significant radical-neutralizing effects, achieving 80.8% (DPPH) and 85.6% (HO) inhibition at a concentration of 60mg/mL. The extract demonstrated a strong, dose-dependent antioxidant profile, albeit with significantly reduced potency compared to ascorbic acid. These findings underscore the extensive bactericidal and oxidative stress-reducing capabilities of S. cumini aqueous leaf extract, affirming its ethnomedicinal significance. Its dual bioactivity facilitates its use in the creation of natural therapeutics and as a functional component in health-enhancing formulations. This research corresponds with SDG 3 (Good Health and Well-being) and bolsters circular bioeconomy initiatives by advocating for the utilization of safe, plant-derived resources for sustainable therapeutic advancement.